The curse of employee privilege: harnessing virtual reality technology to inhibit workplace envy - van Zelderen, Anand Prema Aschwin; Dries, Nicky; Menges, Jochen (Frontiers in Virtual Reality, 2024)
In many workplaces, managers provide some employees with unique privileges that support their professional development and stimulate productivity and creativity. Yet with some employees more deserving of a privileged status than others, co-workers feeling left out of the inner circle may begin to exhibit feelings of envy. With workplace envy and intergroup conflicts going hand in hand, the question arises whether co-worker acceptance of employee privileges-where conflict can be constrained through an affirmative re-evaluation of coworkers' privileged status-may lower the envy experienced by employees. Using virtual reality technology, 112 employees participated in a virtual employee meeting at a virtual organization where they were exposed to a new workforce differentiation practice. We show through our experiment that co-worker acceptance of employee privileges negatively influences workplace envy, which was partially mediated by the anticipated ostracism of employees. Moreover, we show that this effect is only found for employees with privileges, who worry more about being ostracized than their non-privileged co-workers. We anticipate that our findings will enable managers to conscientiously differentiate between their employees, using virtual reality simulations to steer employees' thoughts and feelings in a direction that benefits both employees and organizations.